Comparing and contrasting the effects of aerobic exercise and the exercise mimetic, resveratrol, on neurocognitive function - Hussey, Rosalind Clare (Trinity College (Dublin, Ireland). School of Psychology, 2013)
Excerpt from introduction: Although taken out of context from their use in the opening line of Juvenal’s poem, Satire X, from the late 1st century, these words have often been repeated to promote the belief that only a healthy body can produce or sustain a healthy mind – a healthy mind in a healthy body. It is uncertain who introduced the use of this phrase with its modern day interpretation; however, it extends long before scientific proof was advanced enough to support such a theory. Luckily, we are presently in an epoch that has made, and continues to make, leaps and bounds in research investigating the connection between physical and mental health. There is compelling evidence that a healthy mind is often linked to a healthy body. In humans it is difficult to interpret whether a healthy body encourages mental wellbeing, or whether a healthy mind promotes lifestyle choices that encourage fitness. However, animal studies indicate that forced or voluntary exercise directly enhances cognitive function. The concept of this thesis was to explore how elements of physical and mental health are connected; particularly focusing on the effects that aerobic exercise and resveratrol ingestion have on learning and memory. Research to date indicates that factors that enhance the metabolic system also relieve certain elements of cognitive decline. The extent to which this occurs is still to be determined, with a vast number of scientists investigating different aspects of cognitive decline and methods of altering metabolism. The aim of this thesis is to determine the extent of cognitive enhancement associated with regular resveratrol ingestion and aerobic exercise, and to explore and compare the pathway adjustments that are involved in these actions. A direct comparison study of these two factors will be used in order to highlight more clearly any differences between their actions on the metabolic system and the varying outcome on cognition.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin